PEMBUATAN PELET IKAN APUNG BERBAHAN LOKAL DENGAN TEKNOLOGI STEAMER DI DESA DAHAN REJO, KECAMATAN KEBOMAS, GRESIK - Anam, Choirul; Huda, Miftahul; Amiroh, Ana (Jurnal Pengabdi, 2019)
Dahan Rejo Village, Kebomas District is one of the centers of fish farming centers in Gresik Regency. The obstacle faced by pond farmers is the high price of feed, which increases the cost of production and capital. Farmers have not yet used alternative feed and are still dependent on factory-made pellets. The alternative solution that can be done is to make pellets from local materials such as tofu pellets and corn with steamer technology. The aim of this program is to empower the people of Dahan Rejo Village to make floating fish feed from local materials. The methods used are program preparation, product making and proximate analysis, making tutorial videos and guidebooks, socializing and training, mentoring, monitoring, and evaluating. The result of this community empowerment program is that farmer groups have the potential to develop floating fish pellets. Proximate analysis of floating fish pellets showed protein content of Â 31.6%, 6.8% fat, 4.2% reducing sugar, 4.4% crude fiber, and Ca minerals 0.3%. Tutorial videos and guidebooks for making floating fish pellets are good and suitable for use by the community. Farmers can make pellets from local raw materials independently with the percentage of material achievement being 70% of the total number of group members. The accompanying results show that the obstacles faced by fish pond farmers are weather, supporting raw materials, and marketing. The monitoring and evaluation results show that pond farmers in Dahan Rejo Village are committed to developing floating fish pellets from local raw materials as an effort to sustain the program.